Electrochemical treatment of ex vivo human abdominal skin and potential use in scar management: A pilot study - Dana M Hutchison; Amir A Hakimi; Avin Wijayaweera; Soohong Seo; Ellen M Hong; Tiffany T Pham; Melissa Bircan; Ryan Sivoraphonh; Brandyn Dunn; Mark R Kobayashi; Sehwan Kim; Brian JF Wong (SAGE Publishing, 2021)
Introduction: Scar treatments aim to address pathologic collagen deposition; however, they can be expensive or difficult to control. Electrochemical therapy (ECT) offers a simple alternative treatment. The purpose of this study is to examine the acid-base and histological changes in ex vivo human abdominal skin following ECT. Methods: Forty-two ex vivo human panniculus tissue sections collected from six individuals were tumesced with normal saline. ECT was performed by inserting two platinum needle electrodes connected to a DC power supply into each specimen. Voltage was varied (3-6 V) and applied for 5 minutes. Each specimen was sectioned across both electrode insertion sites and immediately stained with pH sensitive dye. The width of dye color change for each dosimetry pair was calculated. Hematoxylin and eosin staining was used to evaluate samples. Results and Discussion: ECT caused a spatially localised and dose-dependent increased area of acidic and basic pH around the anode and cathode, respectively. A significantly greater mean width of pH change was generated at the cathode compared to the anode in all treatment groups. Histological evaluation displayed broad condensation and hyalinisation of dermal collagen. Conclusion: ECT triggered dermal pH alterations and changed the underlying structural framework of the specimen. This technology may serve as a low-cost, minimally invasive local soft-tissue remodeling technique with potential application in scar management. Level of Evidence: 5 Lay Summary Electrochemical therapy is a novel treatment that causes spatially selective dermal injury in areas of interest. This study measures the effects of electrochemical therapy when applied to abdominal skin. Electrochemical therapy appears to have beneficial effects by causing a highly localised reduction in collagen content or local softening of tissue, which is consistent with other studies on scar therapies, including chemexfoliation, radiofrequency technologies, and lasers. However, electrochemical therapy can be performed at a fraction of the costs of these aforementioned modalities.